Can Niche Dynamics and Distribution Modeling Predict the Success of Invasive Species Management Using Biocontrol? Insights From Acacia longifolia in Portugal - Dinis, Marco; Vicente, Joana R.; César de Sá, Nuno; López-Núñez, Francisco A.; Marchante, Elizabete; Marchante, Hélia (Frontiers in Ecology and Evolution, 2020)
Biological invasions are among the major contemporary threats to biodiversity. Biocontrol has a long history as a safe and effective strategy for the control of invasive species in several world regions, yet the life history and ecological requirements of biocontrol agents are often poorly understood. Species distribution models and assessments of niche overlap and dynamics constitute a way to quantify and compare ecological niches and are widely used for predicting biological invasions. While these tools can also be valuable to predict the effectiveness of biocontrol programs and anticipate whether biocontrol agents can establish on areas targeted for control, they remain underutilized for this purpose. In this work, species distribution models and comparisons of niche dynamics are used to predict the success of the ongoing biocontrol program for Acacia longifolia in Portugal, and potentially along the Mediterranean Basin, using the Australian gall-forming wasp Trichilogaster acaciaelongifoliae, previously released in South Africa. Niches of both the invasive plant and the biocontrol agent were found to be highly similar and to remain conserved through the introduction process. Distribution models identify suitable climatic areas for A. longifolia in 19% of the Mediterranean Basin and predict successful establishment of T. acaciaelongifoliae in 41% of the suitable area for A. longifolia, despite excluding a few locations where very recent establishment occurred. These results allow us to quantify the risk of future A. longifolia invasion and potential success of biocontrol, as well as establish a comparative framework for similar programs being considered in other regions of the world dealing with A. longifolia invasions.